Risk of cardiovascular disease and all cause mortality among patients with type 2 diabetes prescribed oral antidiabetes drugs: retrospective cohort study using UK general practice research database. (3rd December 2009) - Tzoulaki, Ioanna; Molokhia, Mariam; Curcin, Vasa; Little, Mark P; Millett, Christopher J; Ng, Anthea; Hughes, Robert I; Khunti, Kamlesh; Wilkins, Martin R; Majeed, Azeem; Elliott, Paul
Abstract : Objective To investigate the risk of incident myocardial infarction, congestive heart failure, and all cause mortality associated with prescription of oral antidiabetes drugs. Design Retrospective cohort study. Setting UK general practice research database, 1990-2005. Participants 91 521 people with diabetes. Main outcome measures Incident myocardial infarction, congestive heart failure, and all cause mortality. Person time intervals for drug treatment were categorised by drug class, excluding non-drug intervals and intervals for insulin. Results 3588 incident cases of myocardial infarction, 6900 of congestive heart failure, and 18 548 deaths occurred. Compared with metformin, monotherapy with first or second generation sulphonylureas was associated with a significant 24% to 61% excess risk for all cause mortality (P<0.001) and second generation sulphonylureas with an 18% to 30% excess risk for congestive heart failure (P=0.01 and P<0.001). The thiazolidinediones were not associated with risk of myocardial infarction; pioglitazone was associated with a significant 31% to 39% lower risk of all cause mortality (P=0.02 to P<0.001) compared with metformin. Among the thiazolidinediones, rosiglitazone was associated with a 34% to 41% higher risk of all cause mortality (P=0.14 to P=0.01) compared with pioglitazone. A large number of potential confounders were accounted for in the study; however, the possibility of residual confounding or confounding by indication (differences in prognostic factors between drug groups) cannot be excluded. Conclusions Our findings suggest a relatively unfavourable risk profile of sulphonylureas compared with metformin for all outcomes examined. Pioglitazone was associated with reduced all cause mortality compared with metformin. Pioglitazone also had a favourable risk profile compared with rosiglitazone; although this requires replication in other studies, it may have implications for prescribing within this class of drugs.